CONTEXTUAL LEARNING MODEL DEVELOPMENT CITIZENSHIP EDUCATION BASED ON ISLAMIC VALUES IN GROWING RELIGIOUS ATTITUDE - Saleh, Syarbaini; Hajar, Ibnu; Setiawan, Deny (Universitas Dharmawangsa Medan, 2021)
This research is based on problems related to the application of a contextual learning model based on Islamic values to improve students' religious attitudes which have not been maximally carried out so far. The research objective was to find a valid, effective, and practical learning model to improve students' religious attitudes. The methodology used is the Plomp model of research and development (R & D). The research subjects were students of class V Madrasah Ibtidaiyah Negeri Medan City, while the object of this study was the development of a contextual learning model based on Islamic values in fostering students' religious attitudes. The products produced are model books, lesson plans, teacher books, student books, and LAS, the entire product has been validated by design experts, material experts, and linguists then continued with field testing so that it is suitable for use. The research findings show: the product of the contextual learning model based on Islamic values that are produced is valid based on expert validation, has a level of practicality and effectiveness in increasing students' religious attitudes, the ability of teachers to manage learning is a good category and student learning activities during the learning process have increased. The study concludes that the resulting learning model product is valid based on expert validation, has a level of practicality and effectiveness to improve students' religious attitudes. used as a reference for developing a more comprehensive Civic Education learning model.Keywords:Â Contextual, Citizenship Education Based on Islamic Values